A Numerical Investigation on the Hydraulic Fracturing Effect of Water Inrush during Tunnel Excavation - Quan Zhang; Bingxiang Huang; Manchao He; Shan Guo (Geofluids)
When a high-pressure water source is located near a tunnel under excavation, water inrush is commonly associated with a hydraulic fracturing effect. To study the hydraulic fracturing effect of water inrush (HFEWI), flow-rock failure process analysis (F-RFPA2D) was adopted to simulate the water inrush process. The simulated results indicated that a stress disturbance area formed in front of the excavation face and that a hydraulic fracture zone formed in front of the karst cavity. Similarly, stress concentrations formed in front of the excavation face and the karst cavity. The hydraulic fracturing effect was characterized by stress concentration, and the local hydraulic crack propagation was the result of stress concentration. In addition, a pore pressure gradient formed in the crack-free area of the surrounding rock, and the occurrence of hydraulic cracking was the root cause of the significant change in water flow. When the hydraulic cracks initially formed and expanded, the zone of crack activity was large. As the cracks continued to expand, the range of activity decreased and finally concentrated directly in front of the excavation face. Additionally, the shapes of the water inrush channel obtained by the experimentation and numerical simulation were basically the same: semielliptical. During the evolution of hydraulic crack initiation, expansion, and penetration, the bottom of the excavated borehole was initially dry and then experienced seepage and water inrush. Finally, the minimum safe thickness of the rock wall was calculated to provide a safety guideline for this type of water inrush.